First confirmed record of the blue tang, Acanthurus coeruleus (Actinopterygii: Perciformes: Acanthuridae) in the Mediterranean - D. Golani; G. Askarov; B. Appelbaum-Golani (Acta Ichthyologica et Piscatoria, 2015)
A single specimen of a sub-adult specimen of the Atlantic species, Acanthurus coeruleus Bloch et Schneider, 1801, was collected in the Mediterranean coast of Israel. This collection was the first confirmed record of this species in the Mediterranean since hitherto it was known from this region only by a single underwater photograph from Cyprus. We postulate that this species may be considered as having established a population in this region.